Clinical Characteristics and Short-Term Prognosis of Children With Antibody-Mediated Autoimmune Encephalitis: A Single-Center Cohort Study - Kang, Qingyun; Liao, Hongmei; Yang, Liming; Fang, Hongjun; Hu, Wenjing; Wu, Liwen (Frontiers in Pediatrics, 2022)
Background The incidence and prevalence of autoimmune encephalitis (AE) is gradually increasing in pediatric patients (between the ages of 3 months and 16 years). The aim of this retrospective observational study was to investigate the clinical characteristics and short-term prognosis of children with antibody-mediated AE at Hunan Children's Hospital. Methods Antibody analysis of blood and/or cerebrospinal fluid was performed in suspected AE patients admitted to the Department of Neurology, Hunan Children's Hospital from June 2014 to June 2021. Ultimately, 103 patients were diagnosed with antibody-mediated AE and were enrolled in this study. Clinical data and corresponding demographic, clinical characteristics, laboratory and imaging data, treatment, and prognosis data were collected and analyzed. Results In our study, 103 AE patients with antibody-positive were identified. The main subtype of AE in our cohort was anti-NMDAR encephalitis. Few patients have anti-CASPR2 encephalitis, anti-GABABR encephalitis, or anti-LGI1 encephalitis. In our AE patients, the most common clinical manifestations were behavioral symptoms, seizures, and involuntary movements, with seizures being the most common initial symptom. All patients underwent brain magnetic resonance imaging (MRI) and electroencephalography (EEG). Forty-five (43.7%) patients had abnormal MRI findings. And 96 (93.2%) patients had abnormal EEG results. All 103 patients were given first-line immunotherapy, 21 of which were also treated with the combination of the second-line immunotherapy. All surviving patients were followed up for at least 6 months. Seventy-seven patients recovered completely, 23 had sequelae of different degrees, and 3 died. Eight patients had one or more relapses during the follow-up period. Conclusions AE is a treatable disease that can occur in children of all ages. The mortality rate is low, as most patients have a good response to immune therapy. Compared with the older children, infants and young children (≤ 3 years old) with anti-NMDAR encephalitis have a higher incidence of fever and status epilepticus, more severe condition, higher PICU admission rate and worse prognosis. AE patients with high maximum mRS scores and PICU admissions may require second-line immunotherapy.